Analysis Jaringan Sosial Perdagangan Ternak Babi Terhadap Penyebaran Penyakit Classical Swine Fever atau Hog cholera di Kabupaten Sikka Provinsi Nusa Tenggara Timur (NTT), Indonesia. - Petrus Malo Bulu; Ewaldus Wera; Margaretha Sikko (Partner, 2019)
Classical Swine Fever (CSF) is a fatal viral disease of both domestic pigs and wild boar. This disease has become endemic in some districts in Nusa Tenggara Timur. The disease has caused huge economic lossess to pig farmers in NTT including in the district of Sikka in 2017 that was estimated at approximately sixty billion rupiah. Little is known how this disease introduced and transmitted into the region. This research was aimed to identify and analyze the movement of pigs through the market chain as a pathway to spread the disease from outside and within the district of Sikka.A total of 57 respondents were interviewed in this study involved sellers and buyers in the markets (4 buyers and 4 sellers in each market-a total of 32 people), suppliers of pigs (10 people), and pig farmers as many as 5 respondents per village (3 villages selected purposively). A face-to-face interview was conducted to obtain information from the respondents.This study found 5 actors that had the highest Out-Degree values including S5, D1, F24, K1, and P1. The study also found four actors that had the highest betweeness centrality in the network including actors D1, D16, F3 and F30 with their degree of Betweenness centrality of 1532,4, 1265.1, 823.5, dan 738.1 respectively. The network density was 0,12, and diameter was 7. Average geodesic distance was 2,94 (1.26), and overall clustering coefficient of the network was 0,61. The in and out-degree values in the current study suggest that pigs were moving in and out of the areas through the movement of sellers and buyers. The results of the study found that market sellers and buyers are actively moving through the market network, and therefore could potentially contribute to the spread of CSF in Sikka, if an outbreak occurred in the region. This study also found that there was potential movement of pigs in different villages in Sikka through the directed links or ties, which could contribute to the transmission and spread of CSF.